Sports-Related Concussion Among Physically Active Adolescents in the Southeastern United States: Effects on Mental Health During the Pandemic. - Fogarty, Kate; Song, Jihee; Counts, Tara; Grajo, Nicolette; Pracht, Dale; Diehl, David (Child Psychiatry & Human Development, 2026)
Sports-related concussions (SRC) pose risks to young people's physical and mental health. During the COVID-19 pandemic, we studied linkages between youths' SRC experiences and internalizing problems (depression, self-harm, and suicidality) among a representative sample in Southeastern state (n = 4,668 total, n = 547 reported SRC experience). Logistic regressions indicated significant associations between youths' SRC experiences and depression (AOR = 1.32, p <.05), suicidality (e.g., attempted suicide AOR = 2.68, p <.001), and self-harm (AOR = 1.97, p <.001) while controlling for being bullied or teased, gender, age, race, and COVID-19's mental health impact. Contrary to prior findings: (1) SRC associations with self-harm and suicide attempts were consistent across genders; and (2) African American students with SRC were significantly more likely to experience depression, self-harm, suicide planning, and attempts than peers without SRC. Results indicated mental health resilience post-concussion for Latinx youth. Implications advocate population-specific health promotion measures that address vulnerabilities and protective factors while emphasizing SRC education for parents, coaches, and young athletes for timely psychological evaluation and support.